Genome size and base composition variation in natural and experimental Narcissus (Amaryllidaceae) hybrids - Marquéz, I. (2017)
Background and Aims: Although there is evidence that both allopolyploid and homoploid hybridization lead to rapid genomic changes, much less is known about hybrids from parents with different basic numbers without further chromosome doubling. Two natural hybrids, Narcissus alentejanus (2n = 19) and N. perezlarae (2n = 29), originated by one progenitor (N. cavanillesii, 2n = 28) and two others (N. serotinus, 2n = 10 and N. miniatus, 2n = 30, respectively) allow us to study how DNA content and composition varies in such hybrids.Methods: Flow cytometry measurements with two staining techniques, PI and DAPI, were used to estimate 2C values and base composition (AT/GC ratio) in 390 samples from 54 wild populations of the two natural hybrids and their parental species. In addition, 20 synthetic F 1 hybrid individuals were also studied for comparison.Key Results: Natural hybrids presented 2C values intermediate between those found in their parental species, although intra-population variance was very high in both hybrids, particularly for PI. Genome size estimated from DAPI was higher in synthetic hybrids than in hybrids from natural populations. In addition, differences for PI 2C values were detected between synthetic reciprocal crosses, attributable to maternal effects, as well as between natural hybrids and those synthetic F 1 hybrids in which N. cavanillesii acted as a mother.Conclusions: Our results suggest that natural hybrid populations are composed of a mixture of markedly different hybrid genotypes produced either by structural chromosome changes, consistent with classic cytogenetic studies in Narcissus, or by transposon-mediated events. © The Author 2011.